Adaptive Control Strategy for VSC-Based Systems under Unbalanced Network Conditions - Leon, Enrique Andres (2010)
A new adaptive control strategy, intended to improve the ride-through capability of HVDC systems under unbalanced network conditions and parameter uncertainties, is introduced. The proposed strategy resorts to a model reference adaptive control plus a resonant filter. The resonant filter scheme is based on a unique synchronous reference frame that prevents the use of the customary sequence component detector, increasing the controller bandwidth accordingly. Several tests are conducted to compare the proposed scheme against existing HVDC controllers, showing an improved performance regarding: 1) elimination of the 2w ripple on the DC voltage arising during AC-side imbalances; 2) accurate and decoupled active and reactive power tracking when converter parameters are not perfectly known.